2006
DOI: 10.1021/ja057430f
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Structure−Activity Relationship Based Quantification of the Impacts of Enzyme−Substrate Binding on Rates of Peroxidase-Mediated Reactions of Estrogenic Phenolic Chemicals

Abstract: The initial rates of horseradish peroxidase (HRP)-mediated enzymatic reactions of 15 assorted aqueous phase phenolic chemicals were studied. The associated reaction rate constants were found to correlate quantitatively with two independent variables: the highest-occupied molecular orbital energy (E(HOMO)) defining the intrinsic redox reactivities of the phenolic substrates and the distance between a substrate and the deltaN of HIS42's imidazole ring in an HRP/substrate binding complex, obtained through molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 43 publications
3
54
0
Order By: Relevance
“…Similar observations can be made with data published previously by Auriol et al, 2007. Interestingly, k cat is positively correlated with E HOMO (Colosi et al, 2006), which makes sense because k cat and E HOMO relate to the maximum reaction rate potential. It is also determined that k r does not correlate well with E HOMO as shown by Figure 10.…”
Section: Reaction Kinetics Of Estrogenssupporting
confidence: 79%
See 3 more Smart Citations
“…Similar observations can be made with data published previously by Auriol et al, 2007. Interestingly, k cat is positively correlated with E HOMO (Colosi et al, 2006), which makes sense because k cat and E HOMO relate to the maximum reaction rate potential. It is also determined that k r does not correlate well with E HOMO as shown by Figure 10.…”
Section: Reaction Kinetics Of Estrogenssupporting
confidence: 79%
“…Sakurado et al 1990 andBrewster et al 1991 r eported fairly strong correlations with coefficient of 0.86 a nd 0.89 r espectively between compound II reactivity and the E LUMO for sets of substituted phenols. However, Hosoya et al 1983 andColosi et al 2006 reported no significant correlation for a set of similar substrates.…”
Section: Kinetics Determining Factorsmentioning
confidence: 97%
See 2 more Smart Citations
“…Quantum chemical parameters such as E HOMO , E LUMO , qH þ and q À were proved successful in many QSAR studies for characterizing intermolecular electrostatic interactions [26]. The electrophilicity index !…”
Section: Mechanism Consideration and Molecular Structural Parameters mentioning
confidence: 99%